2022
DOI: 10.1017/bpp.2022.20
|View full text |Cite
|
Sign up to set email alerts
|

Can vaccination intentions against COVID-19 be nudged?

Abstract: Once vaccines against COVID-19 became available in many countries, a new challenge has emerged – how to increase the number of people who vaccinate? Different policies are being considered and implemented, including behaviourally informed interventions (i.e., nudges). In this study, we have experimentally examined two types of nudges on representative samples of two countries – descriptive social norms (Israel) and saliency of either the death experience from COVID-19 or its symptoms (UK). To increase the legi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Cheung et al also found no influence from a disclosure statement when a social norm nudge promoted healthier snack choices. Kantorowicz-Reznichenko et al (2022) similarly found no transparency effects on a social norm or two information salience nudges in a vaccination intention study (the nudges were, however, not increasing intentions to begin with). Kantorowicz-Reznichenko and Kantorowicz (2021) did, however, find a decrease in the effectiveness of a disclosed social norm nudge in a stylized lottery choice experiment where the nudge encouraged choosing the highrisk/high-payoff lottery.…”
Section: Empirical Findings About Transparency and Nudgingmentioning
confidence: 94%
“…Cheung et al also found no influence from a disclosure statement when a social norm nudge promoted healthier snack choices. Kantorowicz-Reznichenko et al (2022) similarly found no transparency effects on a social norm or two information salience nudges in a vaccination intention study (the nudges were, however, not increasing intentions to begin with). Kantorowicz-Reznichenko and Kantorowicz (2021) did, however, find a decrease in the effectiveness of a disclosed social norm nudge in a stylized lottery choice experiment where the nudge encouraged choosing the highrisk/high-payoff lottery.…”
Section: Empirical Findings About Transparency and Nudgingmentioning
confidence: 94%
“…However, recent empirical findings suggest otherwise. Notably, in the context of the COVID-19 crisis, evidence for the effectiveness of nudging appears to be mixed at best (Kantorowicz-Reznichenko et al, 2022). Several studies across different national contexts have found that standard nudging methods failed to increase adherence to COVID-19 guidelines (e.g., Blayac et al, 2022;Hume et al, 2021) or decrease vaccine hesitancy (e.g., Moehring et al, 2023;Sinclair and Table 1 Nudging, shoving, and pushing.…”
Section: Nudgingmentioning
confidence: 99%
“…Examining the impact of nudging on actual uptake, Dai et al (2021) report an increase in uptake of 26% for the COVID‐19 vaccine following the use of an appointment reminder nudge, while Kim et al (2018) reported a more modest increase in uptake of 10% for the influenza vaccine, following an intervention where medical staff prompted patients to book their vaccination appointment at the same time as other medical bookings. Returning to intentions, Kantorowicz‐Reznichencko et al (2022, p. 19) find statistically insignificant evidence of saliency nudges changing COVID‐19 vaccination intentions among unvaccinated individuals in (relatively) highly vaccinated countries, and where a significant effect is found, they conclude, “the small effect [size of the nudge] does not seem to be promising.”…”
Section: Sufficiencymentioning
confidence: 99%